Strategies for Converting Non-Edible Biomass into Value-Added Chemicals: Economical and Reliable Biorefining Processes - Kang Hyun Lee; Youngsang Chun; Hah Young Yoo; Seung Wook Kim (BioResources, 2022)
About 35% of global greenhouse gas (GHG) emissions come from the energy sector, which accelerates global warming and sea-level rise. As a renewable resource, biomass not only can replace conventional fossil energy with renewable energy, but it is also a key component of the circular bioeconomy (CBE). To achieve efficient use of bioresources, the concept of biorefinery with CBE strategy is increasingly being considered in several countries. In particular, it aims to reduce crude oil consumption and build an economy that is favorable for the climate and nature by replacing carbon-intensive products such as plastics, synthetic rubber, and synthetic fibers with renewable bio-based resources. The purpose of this article is to investigate biomass conversion technologies for building a CBE and to consider successful biorefinery strategies. In particular, five implications of using biomass are suggested as ways to secure the economic feasibility of biorefinery. We propose a biorefinery that produces value-added chemicals from non-edible biomass through saccharification and fermentation as a strategy to achieve the 2050 goal of net-zero carbon.